A rare case of true broad ligament fibroid in postmenopausal women: a minimally invasive approach - Sai Dhandapani, Kalyani; Jawaharlal, Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine leiomyomas are the most common benign tumors of the female reproductive tract, but broad ligament fibroids are rare, comprising less than 1% of cases. We report a case of a 62-year-old postmenopausal woman presenting with dull abdominal pain and backache. Clinical examination revealed a mobile pelvic mass consistent with a 12-week gravid uterus. Imaging suggested a right adnexal lesion, possibly a complex ovarian cyst or exophytic fibroid, with associated right-sided hydroureteronephrosis. Diagnostic laparoscopy identified a true broad ligament fibroid measuring approximately 6×6 cm. The patient underwent total laparoscopic hysterectomy with bilateral salpingo-oophorectomy and fibroid excision. Histopathology confirmed leiomyoma. Broad ligament fibroids can mimic adnexal masses and pose diagnostic challenges. Laparoscopic excision is a safe and effective treatment in experienced hands.